(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Human beings are gifted with speech through which they can communicate with each other, express their feelings and can do miracles that other species find difficult to do. The journey of communication has been wonderful and amazing one. Man started with some gestures and wall paintings, finally discovered speech. After that development of everything took flight. The planet earth is inhabited by the people who speak different languages but difference of languages could not deter man from maintaining communication with each other. Over the time it is felt that in this business world effective communication is very important. With the ease come some difficulties also. Effective communication also has some hindrances in the way. By adopting some ways we can minimize the risk of failure of communication.